INOVASI DESAIN KUNCI PAS MENGGUNAKAN CATIA V5R20 DENGAN PENDEKATAN ANTROPOMETRI (STUDI KASUS PADA PT. KARYA BAHANA UNIGAM DIVISI PEMELIHARAAN MESIN): Design Innovation of Wrench using Catia V5R20 with Anthropometric Approach (Case Study on PT. Karya Bahana Unigam Machinery Maintenance Division) - Medikano, Alsen; Anissa Aprilya; Azisah , Nur Aini (Jurnal Konversi Energi dan Manufaktur, 2024)
Since the occurrence of the Covid-19 pandemic in early 2020 in Indonesia, it has been necessary to maintain the body's immunity so that it remains stable so that the body is not easily exposed to the virus. For that, PT Karya Bahana Unigam needs to do something that can facilitate the maintenance of press machines by innovating on wrenches as a tool to simplify the machine maintenance process. The innovation that was carried out on this spanner started with distributing questionnaires to machine maintenance operators at PT Karya Bahana Unigam with the aim of knowing the needs of users and knowing the technical characteristics of these innovative products. After making the House of Quality (HOQ), anthropometric calculations are carried out to determine the dimensions of the Wrench innovation product to be made. The results of anthropometric calculations show that the spanner product length is 32.2 cm, the spanner innovation product width is 5 cm, and the spanner product width is 1.34 cm. The design was made using CATIA V5R20 software with a 3-dimensional design form, and drafting was also carried out to find out the design from various views. The folding wrench design consists of 3 components, namely a size 17 spanner, a size 13 spanner, and a pin as a key hinge.